An ultra-low-power bulk-driven subthreshold super class-AB rail-to-rail CMOS OTA with enhanced small and large signal performance suitable for large capacitive loads. (September 2021) - Ghosh, Sougata; Bhadauria, Vijaya
Abstract: This paper introduces a power-efficient super class-AB bulk-driven (BD) operational transconductance amplifier (OTA) in the subthreshold region suitable for driving a high capacitive load. An improved auxiliary differential amplifier is employed using a cross-coupled connection to the gate of the input core differential pairs and its adaptive biasing BD FVF differential pairs to boost the input core transconductance and slew rate in superclass-AB mode. The utilization of a partial positive feedback operation further improves the open-loop voltage gain, overall effective transconductance, and unity-gain frequency (UGF) with a sufficient phase margin of 93⁰. The Post layout simulation results of the proposed OTA in Cadence DFW-II platform using UMC 0.18 μm technology for a 0.5 V single supply and a capacitive load of 200 pF confirm enhancement of 22 times slew rate, 54.32 dB DC gain, and 75 times UGF achieved by the proposed design over its conventional counterpart with only a narrow increase of 1.19 times in power expenditure.